Modulation of function and structure of stratum corneum in sphingomyelin synthase 2-deficient mice. (November 2022) - Honma, Nozomi; Hatta, Ichiro; Okazaki, Toshiro; Tokudome, Yoshihiro
Abstract: Sphingomyelin synthase (SMS) synthesizes sphingomyelin (SM) from ceramide (Cer), a precursor of Cer. The effects of SMS deficiency on stratum corneum (SC) barrier function and SC lamellar structure are unknown. In this report, permeation of hydrophilic and lipophilic compounds through full-thickness skin or stripped skin of SMS2-knockout (KO) and wild-type (WT) mice was examined. Furthermore, small-angle and wide-angle X-ray scattering (SAXS and WAXS) measurements of the SC were performed as a function of temperature to analyze the lamellar structure and hydrocarbon chain packing, where a SC sample was changed from 10 °C to 120 °C at 2 °C/min and the X-ray diffraction profile in the small-angle region and the wide-angle region was observed. Skin permeability of the hydrophilic compound increased significantly for SMS2-KO mice when compared with that of WT mice. In contrast, no difference was observed in the penetration of lipophilic compounds in the skin of both SMS2-KO and WT mice. In SC of SMS2-KO mice, two sharp SAXS peaks were observed due to the lamellar structure with a repetition period of 4.8 nm. The WAXS revealed that the intensity ratio R 0.42/0.37 of the 0.42 nm peak at 2.4 nm –1 to the 0.37 nm peak at 2.7 nm –1 was smaller in the SMS2-KO mouse than in the WT mouse. Due to the temperature dependence of the WAXS, the peaks of 2.4 and 2.7 nm −1 remained until the higher temperatures in SMS2-KO mouse SC than those in WT mouse SC. The results of X-ray diffraction suggest that deficiency of SMS2 may cause the appearance of highly ordered structures of SC, which in turn may reduce the barrier function of SC. Highlights: No difference in skin morphology or epidermal thickness between SMS2KO and WT mice. Permeability of water-soluble model compounds is increased in SMS2KO mice skin compared to WT mice skin. Small-angle X-ray scattering showed a specific sharp peak to the stratum corneum of SMS2KO mice. SMS2KO mouse stratum corneum has a highly ordered structure.